Análise da satisfação dos clientes das academias de ginástica da cidade de João Pessoa (PB) - Aguiar, Fernanda Andrade de (2007)
In globalized world, where the competition quickly grows in all sectors of the economy, it was too important to know what yours customers desire and think. Today the consumers, generally, they are more demanding, and to satisfy them, fully, although is a necessary point it is not easy. The satisfaction research can be seen as a system of analysis of information that catches the opinions of the customer through the evaluation organization performance or, specifically, of its products and services and that they assist the companies to identify new chances and monitor yours performance Therefore, the studies about consumer satisfaction, it is today each time more excellent, as much in the academic scope, as in the enterprise. The main objective of this study was to measure the level of customers satisfaction in the gymnastics academies, of size medium located in the city João Pessoa/PB. To reach the considered objectives, the adopted methodology divided the research in two stages: first, a searches qualitative, and, after that, a searches quantitative. The gotten results in this study had demonstrated that the gymnastics academies come obtaining to satisfy the biggest part of its customers, in relation to many aspects but that they exist, still, some vulnerable points that need to be improved, so that the full satisfaction of same the e is reached, consequently, its together retention to the academy. Analyzing, separately, the level of customers satisfaction of the academies of gymnastics searched, is concluded, still, that each one of them has its peculiarities, with points of prominence and others that they need to be changed so, to take care fully of to the necessities, the academies need to make investments that must be directed for the points in which they present deficiencies and the expectations of the customers.